Edukasi Kesehatan Prostat untuk Meningkatkan Kesadaran Deteksi Dini pada Jemaat GMI Manna Helvetia Medan - Anto, Endy Juli; Siahaan, Jekson Martiar; Fauzi, Tengku M.; Normi, Siti; Panjaitan, Maludin; Hutapea, Kenal P.; Panataria, Lince Romauli; Simanjuntak, Pantas; Sihombing, Parsaoran; Saragih, Meylin Kristina; Manurung, Agnes Imelda; Sitorus, Efbertias; Sitorus, Ragnar Oktavianus; Simatupang, Jones T.; Nababan, Manaor Bismar Posman; Simatupang, Aditia Erick Cantona; Sirait, Kilian; Silalahi, Veraci (Universitas Methodist Indonesia, 2024)
Prostate disease is a significant health concern affecting men, particularly those over 35 years old. This community service activity aimed to increase knowledge and awareness about prostate disease among the congregation of GMI Manna Helvetia Medan through health education. The methods included educational presentations, motivational sessions, and question-and-answer discussions. The activity was attended by 45 participants aged 35-70 years. Results showed improved participant understanding of prostate disease symptoms, risk factors, and the importance of early detection. About 70% of participants committed to undergo prostate examination within the next 6 months. The educational approach through church community proved effective in delivering sensitive health information and raising awareness about the importance of regular check-ups.